A next generation of the schema therapy model of personality pathology: A cross-cultural and international study protocol - Freideriki Carmen Mamali; Marleen Rijkeboer; Dylan Molenaar; Sophie A. Rameckers; Marta Panzeri; Arnoud Arntz; Christopher W. Lee; Robert Brockman; Daniela Ho Tan; Muhammad Kamruzzaman Mozumder; Tarun Kanti Gayen; Dmitry Dyakov; et al. (PLoS ONE, 2026)
Background Personality disorders are highly prevalent worldwide imposing substantial personal and social challenges. Schema Therapy is an effective psychotherapeutic approach for personality pathology and other complex characterological problems. New scientific insights prompted a re-evaluation of its theoretical underpinnings leading to a reformulated Schema Therapy theory. Furthermore, the assumed cross-cultural universality of the Schema Therapy model has not been tested. Aims This project has two primary aims: (1) To develop revised instruments based on the reformulated theory that are psychometrically sound and valid across diverse cultures and languages. (2) To validate the Schema Therapy-related constructs and their inter-relationships across cultures. Methods New draft versions of the Young Schema Questionnaire, Schema Coping Inventory, and Schema Mode Inventory were developed. Before dissemination, these instruments will undergo rigorous psychometric evaluation to refine item sets and ensure linguistic and conceptual consistency. A minimum of 100 adult mental health patients and 100 non-patients from each participating country will complete the revised instruments. Sociodemographic and mental health-related variables will also be assessed. Statistical analyses will evaluate (a) internal consistency, (b) unidimensionality, (c) cross-cultural invariance, (d) factorial validity (if possible), and (e) known-group validity. Malfunctioning items will be deleted, and subscales will be shortened, if possible, targeting internal consistency of ≥.80. Expected outcomes This study is expected to yield optimized versions of the three instruments aligned with the reformulated theory. These findings will inform subsequent international studies to further assess the structural and cross-cultural validity of the revised scales. The resulting empirically validated scales will be openly accessible, facilitating worldwide utilization. Discussion This protocol outlines the first international study based on the reformulated theory, aiming to extend the psychopathological coverage and enhance the cross-cultural application of evidence-based treatments for personality pathology. Results will be disseminated through peer-reviewed publications and conference presentations. Potential limitations are discussed.